Reagent-free LC–MS/MS-based pharmacokinetic quantification of polyhistidine-tagged therapeutic proteins. (February 2017) - Shi, Jianxia; Wong, Jing Man; Ma, Ji; Dickerson, Tiffany; Hall, Colin; Rock, Dan A; Carlson, Timothy J
Aim: Immobilized metal ion affinity chromatography is widely employed for purifying polyhistidine-tagged recombinant proteins from cell lysates. The technique can be applied for quantification of therapeutic proteins in biological matrices by LC–MS/MS.Results: A protein reagent-free workflow was developed for quantifying polyhistidine-tagged proteins by LC–MS/MS. The workflow includes target protein enrichment by immobilized metal ion affinity chromatography, on-bead trypsin digestion and quantification of signature peptides by LC–MS/MS. It was applied to quantify a 6×His-tagged protein in a mouse pharmacokinetic study with assay sensitivity of 10.0 ng/ml and linearity up to 10, 000 ng/ml.Conclusion: The protein reagent-free workflow developed herein can overcome reagent limitation and serve as a viable approach for quantifying polyhistidine-tagged therapeutic proteins to support discovery pharmacokinetic and pharmacodynamic studies.